HOMO ECO-RELIGIOSUS Sebuah Sharing Permenungan, Hipotesis untuk Diskusi - Al. Andang L. Binawan (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2010)
Abstract: For quite a while homo religiosus has been marginalized and trivialized by homo techno-economicus, which gives more emphasis to the corporal and material dimensions of humanity. The negative effects of the techno-economicus paradigm engender the reemergence of homo ecologicus, which offers wisdom of life. Homo ecologicus has also been quite marginalized from the life of humanity. The reemergence of homo ecologicus, in turn, would give a new hope for the reemergence of the face of the homo religiosus, because of its interrelated characteristics with the homo ecologicus. In fact, humans can be called homo eco-religiosus. The close tie between the two needs to be investigated more deeply with the help of philosophy. But, the philosophy we need is not just a Cartesian analytical philosophy, which means a merely intellectual exercise in the public domain. What we need is a philosophy as a philo sophia, love for wisdom, which will lead to an exercise of both feelings and soul in the private domain. Keywords: Homo techno-economicus (techno-economic humans), homo ecologicus (ecological humans), homo religiosus (religious humans), homo eco-religiosus (eco-religious humans), modernitas (modernitiy), religiositas (reli- giosity), filsafat (philosophy), cinta kebijaksanaan (love for wisdom), Henryk Skolimowski.